Recent insights into contributing factors in the pathogenesis of cirrhotic ascites - Li, Zhen; Zhu, Junfeng; Ouyang, Hao (Frontiers in Medicine, 2024)
Cirrhotic ascites refers to the accumulation of fluid in the peritoneal cavity due to severe liver disease and impaired liver function, which leads to poor blood circulation in the body, increased pressure in the hepatic sinus wall, and the exudation of fluid from the plasma into the peritoneal cavity. Cirrhotic ascites is a common complication of cirrhosis and poses a threat to the health and lives of modern people, causing a heavy social burden worldwide. So far, there are no effective treatment methods available to improve the quality and quantity of life for patients and their partners; existing drugs can only alleviate the symptoms of cirrhotic ascites and slow down its progression. This article aims to carefully examine the pathogenesis of cirrhotic ascites by exploring various contributing factors such as portal hypertension, renal dysfunction, inflammation, growth factors, oxidative stress, immunocytes, and gut microbiota. The purpose is to gain better insights and deeper understanding of the mechanisms involved in this condition.